An Insight into the Correlation between Phenolic Content and In vitro Antioxidant Activity of Calocybe Indica Extracts - Le, Trung Hieu; Nguyen, Thi Hong Chuong; Nguyen, Quang Man; Le, Lam Son; Tran, Thi Van Thi; Nguyen, Dang Giang Chau; Nguyen, Minh Nhung; Ho, Xuan Anh Vu; Nguyen, Viet Thang; Nguyen, Chinh Chien; Le, Quyet Van (Letters in Organic Chemistry, 2023)
Calocybe indicahas been considered an essential herb, exhibiting a strong antioxidant capability. To this point, the phenolic compounds could be the primary constituent inducing such high activity. However, the phenolic-antioxidant activity correlation still needs to be understood. This study attempted to shed light on the direct linkage between phenolic compounds and antioxidant activity of the Vietnam-grown Calocybe indicafor the first time. It turns out that the total amount of phenolic content is 97.67 μg/g, which is exceptionally high in the methanol extract. Gallic acid, quercetin, quercitrin, and hesperidin account for 49.02 ± 0.18 μg/g, 15.36 ± 0.24, 18.71 ± 0.32, and 14.58 ± 0.28 μg/g of such activity, respectively. Such antioxidants result in an extraordinary performance in DPPH and ABTS evaluations. Indeed, the total antioxidant capacity ranges from 59.67±0.78 to 91.26±1.57 mg GA/g or from 75.25±0.32 to 88.17±0.64 μmol AS/g, corresponding to the contents of phenolics from 24.92 ±0.24 to 35.28 ± 0.33 mg GAE/g. Furthermore, flavonoid compounds have been quantified to range from 14.63 ± 0.17 to 23.88 ± 0.10 mg QUE/g. These results imply the prominence of Calocybe indicafor biomedical applications.
Keywords: total flavonoid content